Development of INSOL‐tag for proteome‐wide protein handling and its application in protein array analysis. (3rd December 2019) - Fukuda, Eriko; Mori, Masatoshi; Shiku, Hiroshi; Miyahara, Yoshihiro; Kawamura, Yoshifumi; Ogawa, Koji; Ogura, Toshihiko; Goshima, Naoki
Abstract: Proteomic analysis requires protein tags that enable high‐throughput handling; however, versatile tags that can be used in in vitro expression systems are currently lacking. In this study, we developed an insoluble protein tag, INSOL‐tag, derived from human transcription factor MafG. The INSOL‐tagged target protein is expressed in a eukaryotic in vitro expression system and recovered as a pellet following centrifugation at 19, 000 × g for 20 min. Comparisons of the target protein recovery rates of GST‐tag and INSOL‐tag using 111 cytoplasmic proteins revealed a fourfold increase in the yield of INSOL‐tagged proteins. Using 267 cancer antigens purified with INSOL‐tag, we subsequently developed an INSOL‐CTA array method, for profiling autoantibodies in sera of cancer patients. The detection limit of the array was approximately 11.1 pg IgG, and the correlation with ELISA was high ( R 2  = .993, .955). Moreover, when autoantibody profiling of digestive cancer patient sera was performed, antigen spreading was observed. These data suggest that INSOL‐tag is a versatile tag that can insolubilize a wide range of target proteins. It is therefore expected to become a powerful tool in comprehensive protein preparation for protein arrays, antibody production, and mass spectrometry. Abstract : The development of an insoluble tag to accelerate target protein preparation is reported. The tag has a wide range of applications, including the preparation of proteins for protein arrays, antigens for antibody production, and internal standards for mass spectrometry.